Does Simplified Accounting Limit Small and Micro Companies' Access To Bank Financing? - Halina Waniak-Michalak (Journal of Accounting and Management Information Systems (JAMIS), 2017)
Enterprises that use simplified accounting can provide less information to lenders, thereby possibly hampering risk analysis. In this paper I investigate whether simplified accounting is a barrier for Polish Small and Medium-sized Entities (SMEs) enterprises to access financing resources, or makes funding more expensive for them. Telephone interviews with managers of banks and a review of statistical data are used to show that simplified accounting methods may influence the cost of capital of Polish SMEs, but it does not create a barrier to accessing external sources of financing.
Keywords: M21; M41; 650; SME; micro entities; bank financing; simplified accounting; Poland